Covid-19 And Border Restrictions: Tourism and Geopolitical Impact - Asma EDAOUDI; M’bark HOUSSAS; Abdelhaq LAHFIDI (Communications of International Proceedings, 2021)
Tourism is among the sectors most affected by the COVID-19 pandemic, which has impacts on economies, public services and future prospects on all continents. The pandemic is an unprecedented test for public policies around the world; the authorities have made decisions in a situation of great uncertainty. The sudden closure of borders dividing cross-border living areas revealed the contradiction between the reality of people's daily cross-border life, and the obvious lack of coordination of national policies, which does not only seriously disrupted life daily (beyond the legitimate constraints that populations have had to endure everywhere), but also led to the return of negative and erroneous representations of the border and the neighboring country. This article examines the degree of selectivity of border restrictions. While the COVID-19 pandemic is first and foremost a health crisis, its implications have great consequences economically and geopolitically speaking with corresponding implications for travel management and tourism in humanitarian and geopolitical contexts.
Keywords: Tourism; COVID-19 pandemic; Border restrictions; geopolitical contexts.